Influence of Pyrolysis Parameters on the Performance of CMSM - Marta C. Campo; Tymen Visser; Kitty Nijmeijer; Matthias Wessling; Fernão D. Magalhães; Adélio M. Mendes (International Journal of Chemical Engineering)
Carbon hollow fiber membranes have been prepared by pyrolysis of a P84/S-PEEK blend. Proximate analysis of the precursor was performed using thermogravimetry (TGA), and a carbon yield of approximately 40% can be obtained. This study aimed at understanding the influence of pyrolysis parameters—end temperature, quenching effect, and soaking time—on the membrane properties. Permeation experiments were performed with N2, He, and CO2. Scanning electron microscopy (SEM) has been done for all carbon hollow fibers. The highest permeances were obtained for the membrane submitted to an end temperature of 750°C and the highest ideal selectivities for an end temperature of 700°C. In both cases, the membranes were quenched to room temperature.